Memperbaiki pola komunikasi pasangan melalui Behavioral Couple Therapy - Trisna Afdilla (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Communication is one of the keys to establish interaction and solve various problems for husband and wife. Patterns of communication and interaction in couples can affect various aspects of life in the household. Communication patterns in couples determine the quality of the relationship between husband and  wife. When  communication is ineffective, other  problems arise such as the  emergence of negative judgments on partners which results in dissatisfaction with the  marriage. The purpose of this  study  is whether behavioral couple therapy is effective in improving  the communication patterns of married couples. Data  was collected by interview,  observation and  Dyadic  Adjustment Scale. The intervention  was carried  out in 5 stages; lasted for 2 weeks until follow-up. The results of the intervention showed an increase in communication patterns in couples which was marked by an increase in behavioral changes and changes in partner interaction  patterns.